The stigma of mental illness among students and health professionals (Research, Society and Development, 2021)
Introduction: Social stigma is an evil that is still very present in society. The stigma of mental illness is not only present in the social environment, but also intermingles in the health area, being perpetuated, many times, by those who should abolish such stigmatized thoughts, harming the quality of patient care. Objective: This article aims to understand and discuss the stigma related to mental illness in the health area, and its repercussions. Research Method: A narrative bibliographic review was carried out with articles from the last 20 years (2000 to 2020). The databases used were National Library of Medicine (PubMed), Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library Online (SciELO) and “Google Scholar”, using the following keywords and descriptors, with the Boolean operator “e”, “Stigma”, “Prejudice”, “Social exclusion”, “Health”, “Health professional”, “Students”, “Brazilian Psychiatric Reform”, “Psychosocial care network”, “RAPS”, “Mental Illness”, “History of psychiatry”. Results and Discussion: The stigma related to psychiatric disorders has been perpetuated for ages, to a greater or lesser extent, being more effectively combated only from the middle of the last century. However, there is still a considerable remnant of this stigma, which is even present in the medical environment, fueling negative attitudes against psychiatric patients, even affecting the quality of a possible treatment. Conclusion: Although it is still a significant problem, there are currently great and effective efforts to reduce the stigma of mental illness.